On the HPC/HPDA/AI Competences in Bulgaria - Karaivanova, Aneta; Atanassov, Emanouil; Gurov, Todor (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2022)
EU member states and the European commission realized the importance of High Performance Computing (HPC) and its applications in High- Performance Data Analytics (HPDA) and Artificial Intelligence (AI) and provided substantial funding for buying hardware and developing the national competences in the area. The EuroCC project (https://www.eurocc-access.eu/) supported the establishment of National Competence Centres in HPC/HPDA/AI, which serve as a focus point for access to expertise and know-how in the area and foster the European collaboration in the area. Bulgaria tries to maintain a leading position in the area of HPC in the region and thus it is important to collect and analyse information about the available competences in the field, the demand from the research community and the private sector, and to map ways for future development. The paper gives an overview on the current competences in HPC, HPDA and AI in Bulgaria and provides information about the plans for future development.